Efficacy and Complication of Rubber Band Ligation of Hemorrhoids in Out Patient Clinic in Al-Muthanna Province - Faeq Sadeq, Ali; Ali Al-Hamdani, Hussein; Najee, Haifaa (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The rubber band ligation nowadays is one of the most effective worldwide techniques used for the treatment of hemorrhoids. The objective of this study is to determine the outcome of the endoscopic band ligation in patients with internal hemorrhoids. Patients and Methods: This observational and prospective study was done for 159 patients with 1st, 1st,2nd,3rd,degree hemorrhoids between 1st June 2015 and 31st June 2018 in outpatient clinics in Almuthanna province. Any complicated piles, such as those with fistula, fissure, and malignancy, were excluded. Our patients followed up in one month, six months, and one year and then yearly by telephone. Result: From 159 patients with a mean age of 44.28 (range 18-89), recurrence occurs in 21 (13.2) cases. postoperative bleeding in 4 cases (2.5%) and pain in 7 cases (4.4), vasovagal syncope in 4 cases (2.5%), and infection in 2 cases (1.3%). Conclusion: Rubber band ligation is an effective, outdoor procedure for symptomatic 3rd degree hemorrhoids with acceptable morbidity